Optimalisasi Hidrolisis Umbi Talas Beneng (Xantoshoma undipes K. Koch) sebagai Bahan Baku Bioetanol - Visiamah, Fenti; Simanjuntak, Wasinton (ALKIMIA, 2020)
This study conducted to assess the most appropriate method or hydrolysis of beneng taro tuber to optimize the production of bioethanol to investigate the effect of pHs, times, and temperatures on reducing sugar produced. The concentration of reducing sugar was determined using a UV-Vis spectrophotometer. The result obtained indicated that the optimum amount of reducing sugar (910,875 mg/L ) achieved at pH 10, hydrolysis time of 3 hours, and the temperature of 90 °C. Fermentation of reducing sugar using the powdered bark of raru plant produced 0,18765 % (v/v) of bioethanol and fermentation using Saccharomyces cerevisiae produced 0,2116 % (v/v) of bioethanol.